Komunikasi Organisasi Education Management Information System (EMIS) Bidang Pendidikan Agama dan Keagamaan Islam (PAKIS) Dalam Meningkatkan Registrasi Pondok Pesantren di Kanwil Kemenag Provinsi Sumatera Selatan - Rizki Ulandari; Hamidah; Anang Walian (CV. ITTC INDONESIA, 2023)
This research is about how the Organizational Communication of EMIS Pontren of the Ministry of Religion in providing information on Islamic Boarding Schools data collection as well as the supporting and inhibiting factors in providing Islamic Boarding Schools Institution data collection information. The communication strategy built by the EMIS Pontren relationship can add trust to Islamic Boarding Schools Institutions and the public so as to create a separate positive image of a Government Intitution. The positive image that is built needs to be maintained because it has a role and reputation for government. This study uses a qualitative research method with the data obtained in the form of documents, observations, and direct interviews. The purpose of this study was to find out how the EMIS of Islamic Boarding Schools provided registration information for Islamic Boarding Schools at the Office of the Ministy of Religion of South Sumatera Province and what were the supporting and inhibiting factors for EMIS in providing information.The result of this study are the EMIS Pontren Organization Communication in providing Islamic boarding schools data collection information, namely knowing communication targets, compiling messages, eatablishing metdos, and choosing strategic communication media in public relations activities based on interwiews conducted by researcher, namely reducing, canalizing, informative, persuasive, educative strategy which is used in its application in carrying out the vision and mission that has been designed by the agency, this strategy has helped agencies, especially in the field of service and providing information on EMIS Pontren PAKIS